Intracellular NAD+ Depletion Confers a Priming Signal for NLRP3 Inflammasome Activation - Shim, Do-Wan; Cho, Hyo-Joung; Hwang, Inhwa; Jung, Taek-Yeol; Kim, Hyun-Seok; Ryu, Ju Hee; Yu, Je-Wook (Frontiers in Immunology, 2021)
Nicotinamide adenine dinucleotide (NAD+) is an important cofactor in many redox and non-redox NAD+-consuming enzyme reactions. Intracellular NAD+ level steadily declines with age, but its role in the innate immune potential of myeloid cells remains elusive. In this study, we explored whether NAD+ depletion by FK866, a highly specific inhibitor of the NAD salvage pathway, can affect pattern recognition receptor-mediated responses in macrophages. NAD+-depleted mouse bone marrow-derived macrophages (BMDMs) exhibited similar levels of proinflammatory cytokine production in response to LPS or poly (I:C) stimulation compared with untreated cells. Instead, FK866 facilitated robust caspase-1 activation in BMDMs in the presence of NLRP3-activating signals such as ATP and nigericin, a potassium ionophore. However, this FK866-mediated caspase-1 activation was completely abolished in Nlrp3-deficient macrophages. FK866 plus nigericin stimulation caused an NLRP3-dependent assembly of inflammasome complex. In contrast, restoration of NAD+ level by supplementation with nicotinamide mononucleotide abrogated the FK866-mediated caspase-1 cleavage. FK866 did not induce or increase the expression levels of NLRP3 and interleukin (IL)-1β but drove mitochondrial retrograde transport into the perinuclear region. FK866-nigericin-induced mitochondrial transport is critical for caspase-1 cleavage in macrophages. Consistent with the in vitro experiments, intradermal coinjection of FK866 and ATP resulted in robust IL-1β expression and caspase-1 activation in the skin of wild-type, but not Nlrp3-deficient mice. Collectively, our data suggest that NAD+ depletion provides a non-transcriptional priming signal for NLRP3 activation via mitochondrial perinuclear clustering, and aging-associated NAD+ decline can trigger NLRP3 inflammasome activation in ATP-rich environments.